The Influence of Institutional Ownership, Managerial Ownership, and Board of Commissioners on Agency Costs (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to determine the effect of institutional ownership, managerial ownership, and the board of commissioners for agency costs in basic industrial sector companies and chemicals listed on the Indonesia Stock Exchange for the period 2015-2019. The independent variables used in this study are institutional ownership, managerial ownership, and the board of commissioners. Meanwhile, agency cost is the dependent variable used in this study. Secondary data is the data used in this study with a total of 60 companies used as a population and 15 companies used as samples in companies in the basic industry and chemical sectors. This study uses multiple linear regression and statistical analysis methods of classical assumption test data. The results of this study indicate that institutional ownership has a positive influence on agency cost. However, managerial ownership and board of commissioners variables have a negative effect on agency cost.